Transmission Dynamics of Respiratory Viruses in a Congregated Military Population: Prospective Cohort Study. (4th October 2017) - Lewnard, Joseph; Chen, Wei-Ju; Milzman, Jacqueline Owens; Grigorenko, Elena; Robinson, Scott; Jones, Carol; Moreno, Nicole; Malone, Leslie; Weinberger, Daniel M; Burgess, Timothy; Coles, Christian
Abstract: Background: Human coronaviruses (HCoVs), rhinoviruses, and non-polio enteroviruses (NPEVs) are leading causes of seasonal acute respiratory infections among children and adults, posing significant health and economic burden annually. Despite this, little is known about their epidemiological dynamics, including the role of asymptomatic shedding in transmission; the durations of virus incubation and shedding; and the effect of immune responses on risk for re-infection during the same season. We studied respiratory virus shedding in military recruits, and used mathematical models to measure pathogen-specific transmission rates and durations of incubation, shedding, and immune protection. Methods: We tested for shedding of HCoVs, rhinoviruses, and NPEVs in nasal samples collected from 78 military recruits entering basic training and then at staggered, biweekly visits over 65 days during winter 2017. We developed a continuous-time Markov chain model for virus acquisition and clearance, and used Bayesian methods to estimate model parameters for each of HCoV-229E, HCoV-OC43, rhinoviruses, and NPEVs. Results: We observed widespread transmission of HCoV-229E, rhinoviruses, and NPEVs within the first week after entry into basic training, and a subsequent phase of transmission predominantly involving HCoV-OC43 during the second month (Figure ). We estimated pre-epidemic reproductive numbers ranging from 1.97 (95% credible interval: 1.49, 2.60) for HCoV-OC43 to 5.69 (3.92, 7.98) for HCoV-229E (Table ). Subjects re-acquired HCoV-229E, rhinoviruses, and NPEVs despite previous exposure; for these pathogens, we estimated reversion to pre-infection susceptibility to occur, on average, 28.5 (15.8, 49.7) days, 52.2 (22.3, 151.1), and 144.7 (61.3, 812.5) days, respectively, following clearance of viral shedding. Conclusion: Asymptomatic shedding is a source of transmission of common respiratory viruses in the close-contact basic training environment. Protection against re-acquisition is short-lived, and may be inadequate to prevent re-infection by rhinoviruses and NPEVs within a season. Estimated durations of shedding and incubation periods provide a basis for modeling pathogen spread and informing isolation protocols. Disclosures: J. Lewnard, Pfier: Grant Investigator, Research grant. E. Grigorenko, Diatherix Laboratories: Employee, Salary. D. M. Weinberger, Pfizer, Merck, Affinivax: Consultant and Grant Investigator, Consulting fee and Research grant.